Interaction effects of country-level governance quality and debt on stock returns in developing nations - Matemilola, Bolaji Tunde; A. N, Bany Ariffin; Md.Nassir, Annuar (2018)
This study examines the moderating effects of country-level governance quality on the relationship between debt and stock returns, using 3,891 firms from 23 developing countries covering the period from 2006 to 2014. Applying the panel generalized method of moments to control for endogeneity, the findings reveal that country-level governance quality has positive moderating effects on the relationship between book debt and stock returns. Robustness check using market debt show that country-level governance quality has positive moderating effects on the relationship between market debt and stock returns. Additional analysis controls for the financial crisis years and the results are broadly similar, except that the coefficients of some variables change. The results suggest that strong governance quality lowers financial risk which encourage firms to raise debt capital needed to maximize stockholders’ returns.